Spectatorship Ethnography - Bambang Sukma Wijaya (I-Pop: International Journal of Indonesian Popular Culture and Communication, 2020)
This article explores spectatorship as a phenomenon within communication, branding, and media/cultural studies through a participant ethnographic approach applied to communal viewing (nobar) activities. Departing from the premise that watching is not merely a passive act of reception, this study integrates three conceptual frameworks (audience desire and pleasure, memory spectacles, and the unconscious dream) to understand how spectators merge with and engage affectively with media texts and narratives. Through participant observation during communal viewing moments, the researcher examines viewers' behaviors, feelings, and thoughts as they encounter specific media content, capturing engagement dynamics that are simultaneously cognitive, emotional, and unconscious. A psychoanalytic lens is employed to read how viewing reflects viewers' latent desires and personal fantasies. At the same time, the concept of memory spectacles traces how the viewing experience triggers the resurfacing of personal and collective memories that are performed and displayed within the social interactions of communal viewing. Viewing pleasure is understood as arising from the release of desire that occurs when the boundary between the viewer's self and the media text dissolves, producing an immersive experience that transcends mere information consumption. This ethnographic approach is considered particularly suited to delving into the attitudes and experiences of audiences, consumers, participants, and publics toward viewing materials with specific content and narratives, including how such engagement carries over into and persists within their everyday lives. This article contributes to communication and branding studies by offering an analytical model that integrates the affective, psychological, and sociocultural dimensions of spectatorship, while affirming the importance of participant ethnography as an instrument for uncovering layers of meaning that surveys or textual analysis alone cannot capture. Its implications are relevant for media practitioners, brand marketers, and popular culture researchers seeking to understand audiences' emotional attachment to what they watch.